2019
DOI: 10.5830/cvja-2018-074
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of risk-factor profile in Egyptian patients with acute coronary syndrome: phase II of the Egyptian cross-sectional CardioRisk project

Abstract: Background: Egypt is the most populous country in the Middle East and North Africa and has more than 15% of the cardiovascular deaths in the region, but little is known about the prevalence of traditional risk factors and treatment strategies in acute coronary syndrome (ACS) patients across Egypt. Methods: From November 2015 to August 2017, data were collected from 1 681 patients with ACS in 30 coronary care centres, covering 11 governorates across Egypt, spanning the Mediterranean coast, Nile Delta and Upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 28 publications
5
25
0
Order By: Relevance
“…Of particular concern is tobacco use, which was ubiquitous among males across the 4 regions. In the Egyptian cross-sectional CardioRisk project [8], 62% of men and 5% of women presenting with ACS were current smokers. Exposure to smoking in Egypt is high across all wealth categories as reported in the Egyptian Health Issues Survey in 2015 [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular concern is tobacco use, which was ubiquitous among males across the 4 regions. In the Egyptian cross-sectional CardioRisk project [8], 62% of men and 5% of women presenting with ACS were current smokers. Exposure to smoking in Egypt is high across all wealth categories as reported in the Egyptian Health Issues Survey in 2015 [9].…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of the Egyptian cohort was 10-year youngers than that of the rest of the ESC-HF-LT Registry regions, but similar to that of patients in the Saudi HF registry [ 7 ]. In the Egyptian cross-sectional CardioRisk project, premature ACS was highly prevalent in Egyptians, seen among 46% of men aged less than 55 years and in 67% of women aged < 65 years [ 8 ], and this could be considered a potential contributing factor to the earlier presentation for HF seen in the Egyptian cohort. Within our study’s cohort, the mean age varied by almost 10 years between regions, with the highest age in Alexandria, 62.3 (± 11.6) years, and the lowest in Upper Egypt, 51.2 (± 11.2) years ( P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“… 2 However, it is similar to the reported age from south Asia and Egypt. 18 , 19 These findings may indicate a higher genetic risk, lack of preventive care and or a need for addressing modifiable risk factors in our population.…”
Section: Discussionmentioning
confidence: 92%
“…The high prevalence of CVD risk factors [ 47 49 ] in certain countries outside Western Europe and North America contributes to premature atherosclerosis and an earlier onset of ACS and higher age-standardised mortality rates from ischaemic heart disease [ 50 ] in these regions. This includes the higher prevalence of FH in some regions as a result of founder effects (e.g.…”
Section: Barriers To Optimal Dyslipidaemia Management Post Acsmentioning
confidence: 99%
“…For example, at 51.2 ± 10.3 years, the mean age for first presentation of acute MI in Middle Eastern countries is around 10 years younger than that reported in other regions of the world [ 49 , 53 ]. The Egyptian CardioRisk project reported that premature ACS was common: of 1681 patients admitted to hospital with ACS, 43% of men were aged < 55 years, and 67% of women were aged < 65 years [ 47 ]. A study of South African Asian Indian patients with ACS reported mean ± standard deviation age at presentation as 54.6 ± 10.9 years [ 52 ].…”
Section: Barriers To Optimal Dyslipidaemia Management Post Acsmentioning
confidence: 99%